Modernos brasileiros +1: um olhar sobre uma exposição de design no Museu Oscar Niemeyer - Guterres, Georgia Graichen Bueno (2020)
This research aims to study versions of Brazilian design that were presented at a furniture exhibition. The idea is to understand in which ways thi furniture exhibition, presented in the largest museum in the state, can be explored by aspects other than the canonical of the history of the design. And how the research universe is represented and what institutional, personal and circulation and consumption of artifacts relationships presented in the exhibition can be seen through the material surveyed. “Brazilian moderns +1” was an exhibition of modern furniture design exhibition held at the Museu Oscar Niemeyer in 2010. The concept of curatorial argument affiliated with this research and the expographic elements considered were defined from the discussions around the use of scenographic resources established mainly by Gonçalves (2004) and Meneses (2013). The thinking of design versions is based on authors like Campi (2013), Niemeyer (2000) and Forty (2013). For the analysis of this work, we opted for a cross-checking methodology between bibliographic references, official documentation on the exhibition and interviews with the exhibition’s interlocutors. The interviews are based on oral history with the main reference in studies of Alberti (2008). This crossing made it possible to think about other ideas about the history of design present in the exhibition that run away from the canonical concepts presented in history of traditional design.